Implementasi Deep Learning Berbasis Media Interaktif Pada Pembelajran IPAS Siswa Sekolah Dasar - Hana Fatimah; Nining Setyaningsih; Fajar Sri Utami; Tutik Ernawati; Budi Murtiyasa (Jurnal Penelitian Pendidikan IPA, 2026)
The development of educational technology has encouraged the need for learning innovations that can improve conceptual understanding and student engagement, especially in science subjects in elementary schools. This study aims to analyze the effect of the implementation of interactive media-based deep learning on learning outcomes and student engagement in Grade IV students. The study used a quantitative approach with a one-group pretest–posttest design involving 30 students at MI Muhammadiyah Tahfidzul Qur'an. The instruments consisted of a learning outcome test and an activity observation sheet. Data analysis was carried out using a paired sample t-test and effect size calculation. The results showed a significant increase in learning outcomes, from 64.40 to 77.20 (t = -22.06; p = 0.000), and an increase in student activeness from 60.40 to 78.77 (t = -24.252; p = 0.000). The very large effect size values (d = 4.02 for learning outcomes and d = 4.24 for student activeness) indicate that the learning influence is very strong and practically meaningful. These findings confirm that interactive media-based deep learning is effective in improving academic achievement and active student participation, making it suitable for implementation as a learning strategy in the science subject in elementary schools.